NOSOTROPIC SUBSTANTIATION OF ANTI IgE ANIBODY THERAPY - Yu.G. Levina (Union of pediatricians of Russia, 2008)
This article studies the specifics of allergic diseases pathogenesis. Such common allergic diseases as bronchial asthma, allergic rhinitis and atopic dermatitis are conditioned by processes based on increase of immunoglobulin e synthesis. Omalizunab, which is a recombinant humanized monoclone anti-Ige antibody, prevents Ige fixing to membrane receptors of mast cells and significantly reduces the level of immunoglobulin e circulating in blood.Key words: anti-Ige antibody, omalizumab, allergic diseases, Bronchial asthma, children.